Implementasi Recycle dalam Meningkatkan Partisipasi Masyarakat Peduli Sampah di Komunitas Pasar MMTC - Silvia Mariah Handayani; Alfyiona Gabriella Br Ginting; Ayu Wulandari Siregar; Esra Haniarta Saragih; Rosita Oktaviani Sinaga; Swarni Vofvi Maharani Sitanggang (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Indonesia faces big challenges in waste management, with waste volumes continuing to increase every year. As a densely populated island country, factors such as rapid population growth, urbanization, changes in consumption patterns, and a lack of waste management infrastructure have also exacerbated this condition. Based on observations at the MMTC market, the rubbish problem is very serious due to the large amount of rubbish strewn about that is not cleaned up by traders. This research aims to explore efforts to increase education and training about recycling for the community, increase community participation in maintaining cleanliness through recycling activities in market communities, develop an efficient and effective recycling management system, and identify barriers to implementing recycling programs. reset on the MMTC market. The expected output of this research is increasing public awareness and participation in maintaining market cleanliness through recycling activities, comprehensive research results reports, and publication in SINTA indexed journals. It is hoped that this research can be an important step in efforts to create a cleaner and more sustainable market environment in Indonesia.